Layanan Angkutan Online Kota Medan Perlindungan Hukum Bagi Pengemudi - Purba, Bonaraja; Hasyim, Hasyim; Purba, Kristin Yenita; Zebua, Nobel Indah Clawdya; Amanda, Sophia; Manurung, Zenifer (LPPM Universitas Labuhanbatu, 2023)
Legislation in the social planning process influences the formulation of regulations to manage social change in society, for example through the implementation of community-wide legal protections. The relationship between online transportation service providers and online transportation services is regulated in the Civil Code and specifically the elements of the legal meeting of official partners: trustworthiness, order and wages. The purpose of this research is to find out how long the regulation will remain in effect, and whether the law will be respected and its protection guaranteed. community protection. This research is qualitative in nature. In other words, you can overcome research challenges based on legal principles, doctrines and legal regulations.Â